Capital Gains Tax-Capita Selecta on capital losses - Broekmann, Trudie (Department of Commercial Law, 2023)
The taxation of capital gains was introduced into the South African taxation law with the promulgation of the Taxation Laws Amendment Act, No. 5 of 2001